PENGARUH PARAMETER PROSES 3D PRINTING TERHADAP KEKUATAN IMPAK MENGGUNAKAN METODE CHARPY PADA FILAMEN PLA - Ongki Rio Irfany; Zaldy Sirwansyah Suzen; Ariyanto Ariyanto (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
The existence of 3D Printing technology in the manufacturing sector has brought big changes to the industrial world This research uses a 3D printing machine FDM model PRUSA area with dimensions of 220mm X 220mm X 250mm with a nozzle diameter of 0.4mm. The material used is a PLA filament with a diameter of 1.75mm with a variety of parameters, namely infill geometry (Grid, Lines, Triangles, Tri Hexagon, Cubic, Cubic Subdivision, Octet, Quarter Qubic, Concentric, Zig-Zag, Cross, Cross 3D and Gyroid), printing speed (40mm / s, 50mm / s and 60mm / s), flowrate (80%, 90% and 100%) and colling speed (40%, 50% and 60%) which are specified in ultimaker cura 4.7.1 so that produced 39 printed samples. The highest impact test results were found in the test specimen number 6 cubic subdivision of 0,00935 Joule/mm2 with a printing speed of 40, flowrate 80 and colling 40. The lowest impact test value in experiment number 24 cross is 0,00066 Joule/mm2 with a printing speed of 50, flowrate 90 and colling speed 50.